TEACHING CHALLENGES ENCOUNTERED BY ENGLISH TEACHER IN IMPLEMENTING STUDENT LED-LEARNING METHOD - Ni Kadek Diantari (Journal of English Education and Literature, 2024)
Teaching challenges involve situations and opportunities that require teacher to make special efforts to obtain something. Teaching English will be difficult to learn without preparation before carrying out activities because a lack of knowledge will cause problems in the teaching and learning process. In teaching a foreign language, it is important to ensure that we understand the best approaches, methods and strategies to use so that learning English becomes easy and interesting. This research aims to identify students' metacognitive strategies used in completing reading assignments. The subject of the research participant of this research was the eleventh semester students and one teacher of Pasraman Vidya Sthana Suranadi was chosen as the sample of the study. The participant of this research was the sixth semester students of English Language Education Department who worked in teaching practicum. This research uses a descriptive qualitative research design and uses in-depth semi-structured interviews as a research method to collect data. This research uses a descriptive qualitative research design and uses in-depth semi-structured interviews as a research method to collect data. This research found that teachers found challenges in teaching English before using the Student Led-learning method, and after using the Student Led-learning method, teachers felt that they faced fewer challenges. Overall, the findings of this study indicate that the use of Student Led learning in English language teaching can overcome the teaching challenges faced by English teachers, and it is important for teachers and counselors to introduce and train students in using this method.